Clear cell meningioma of the filum terminale in a 44-year-old woman: case report - Glinka, Piotr; Sobstyl, Michał; Acewicz, Albert; Bojarski, Piotr (Folia Neuropathologica, 2024)
Clear cell meningioma (CCM) is a rare subtype of meningioma, especially unusual as a neoplasm of the filum terminale. Clear cell meningioma seems to have a more aggressive nature and a higher risk of recurrence than WHO grade I meningiomas. A 44-year-old woman presented with lower back pain radiating to the left leg and mild weakness in the left leg. Magnetic resonance imaging (MRI) showed a well-demarcated, intradural lesion filling the spinal canal at the L3-S1 levels and compressing the cauda equina. The patient underwent laminectomy from L3 to S1. During the operation, the filum terminale was identified as a structure that was disappearing into the tumor. The filum terminale was cut and the tumor was totally removed in one piece. Pathological findings were indicative of the diagnosis of clear cell meningioma, CNS WHO G2. Postoperative magnetic resonance imaging at 6 months showed no residual mass. Total surgical excision of the CCM of the spinal cord should be chosen as the optimal treatment. In addition, radiological follow-up is equally important due to the high risk of recurrence. Our case is unusual in that the tumor’s location was the filum terminale.